Nervous system injury in alcoholic disease - O. E. Zinovyeva (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2019)
The paper considers various variants of nervous system injury in alcoholic disease. It discusses the epidemiology, pathogenesis, diagnosis, and clinical manifestations of central and peripheral nervous system lesions in the presence of acute and chronic alcohol intoxication. Attention is paid to the issues of etiotropic, pathogenetic, and symptomatic treatment for neurological manifestations of alcoholic disease and to the role of neurotropic B vitamins in the treatment of alcohol-induced deficiency and non-deficiency states.